2021
DOI: 10.1073/pnas.2018090118
|View full text |Cite
|
Sign up to set email alerts
|

Sialoglycan recognition is a common connection linking acidosis, zinc, and HMGB1 in sepsis

Abstract: Blood pH is tightly maintained between 7.35 and 7.45, and acidosis (pH <7.3) indicates poor prognosis in sepsis, wherein lactic acid from anoxic tissues overwhelms the buffering capacity of blood. Poor sepsis prognosis is also associated with low zinc levels and the release of High mobility group box 1 (HMGB1) from activated and/or necrotic cells. HMGB1 added to whole blood at physiological pH did not bind leukocyte receptors, but lowering pH with lactic acid to mimic sepsis conditions allowed binding, impl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…2020 ), it remains to be seen if some of the more recent infectious variants have regained these residues. There may also be other effects of Sias such as on immune recognition given that sialoglycans serve as self-associated molecular patters (SAMPs) ( Varki 2011 ) and/or in COVID-19-associated inflammation ( Siddiqui et al. 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2020 ), it remains to be seen if some of the more recent infectious variants have regained these residues. There may also be other effects of Sias such as on immune recognition given that sialoglycans serve as self-associated molecular patters (SAMPs) ( Varki 2011 ) and/or in COVID-19-associated inflammation ( Siddiqui et al. 2021 ).…”
mentioning
confidence: 99%
“…While prospective trials of zinc supplementation are underway ( Perera et al., 2020 ), existing retrospective meta-analyses have given inconsistent results ( Fromonot et al., 2021 ; Dubourg et al., 2021 ; Wessels et al., 2021 ; Szarpak et al., 2021 ). We recently discovered that HMGB1 can be functionally sequestered away from its activating receptors by plasma sialoglycoproteins in a zinc-dependent manner, a protective effect that is lost when blood pH falls due to lactic acidosis ( Siddiqui et al., 2021 ). Current trials independently studying zinc supplementation, HMGB1 inhibition, or pH normalization may be more successful if these approaches are combined and perhaps supplemented by infusions of heavily sialylated forms of glycoproteins like CD52 ( Shathili et al., 2019 ).…”
mentioning
confidence: 99%
“…The level of HMGB1 is closely related to the prognosis of sepsis. It is an important member of the alarm hormone in vivo [ 33 ]. As a typical alarm protein [ 34 ], the HMGB1 can induce inflammation after transfer to the outside.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 plays a role in several cellular processes, including inflammation, cell differentiation and migration [ 32 ]. In our previous study, the upregulation of HMGB1 was found to be strongly correlated with cirrhosis in HCC [ 21 ].…”
Section: Discussionmentioning
confidence: 99%